Caracterização do Pythium insidiosum por abordagem proteômica - Chechi, Jéssica Luana [UNESP] (2016)
Pythiosis, whose etiologic agent is the oomycete Pythium insidiosum, is a disease that affects several animal species, including human, being more prevalent in horses. The disease has difficult diagnosis and treatment. Studies on protein characterization of P. insidiosum are scarce. The objective of this study was to determine the protein profile of Pythium insidiosum by mass spectrometry and bioinformatics strategies aiming to identify virulence factors. To this end, an extraction was standardized technique of total proteins of P. insidiosum, which were quantitated. From the protein extraction protocol it was obtained the profile of proteins expressed by the oomycete P. insidiosum through analysis by two-dimensional electrophoresis. The gels had 186 spots analyzed with molecular weight 12-89 kDa and an isoelectric point of 4-7, 103 of these were cut and sequenced. A total of 36 proteins were identified and grouped according to their functions, six of them were classified as proteins related to virulence - β 1,3 glucan synthase, Hsp 70, enolase, peroxiredoxin 2, G protein and the proteasome β unit. The results of this work will contribute to better understanding of the pathogenic mechanisms of P. insidiosum as well as for further studies in the therapeutic field and diagnosis.